Gastroparesis managed with peroral endoscopic pyloromyotomy. Issue 1 (2nd January 2020) - Clothier, Jessica S.; Leeds, Steven G.; Ebrahim, Ahmed; Ward, Marc A.
Abstract: Gastroparesis is delayed gastric emptying in the absence of mechanical obstruction. Cases are attributed to narcotic use, smoking, diabetes, and postsurgical complications; however, several incidences are unknown. Treatment options include diet modification, gut-stimulating medications (e.g., metoclopramide, domperidone), laparoscopic pyloroplasty, and, in the most severe cases, partial gastrectomy with Roux-en-Y reconstruction. Recently, a novel therapy has been developed, peroral endoscopic pyloromyotomy (POP). This procedure is similar to a laparoscopic pyloroplasty; however, it is performed completely endoscopically, thus negating the need for incisions. Here we present a case of gastroparesis treated with this novel technique.